A Public Praise with Neither Purse Nor Scrip: Old Elizabeth and Womanist Theological Ways - Pierce, Yolanda Nicole (Theology today, 2013)
Using Scripture to contest eighteenth- and nineteenth-century societal norms, Elizabeth’s memoir of her life in slavery contests the legal and cultural structures that rendered her as secondary, inferior, and subhuman. In answering the call to public ministry, Elizabeth embodies womanist ethics by being outrageous, audacious, and courageous in spite of the vocal opposition to her ministerial vocation.